The Influence of Principal Supervision and Teacher Training on the Pedagogical Competence of Teachers at State Madrasah Aliyah in Pekanbaru City - Daulay, Iwan Salih Hamonangan; Azhar, Fadly; Sumarno , Sumarno (Journal Corner of Education, Linguistics, and Literature, 2025)
This study examined the impact of principal supervision and teacher training on the pedagogical competence of educators at State Islamic Senior High Schools (Madrasah Aliyah Negeri) in Pekanbaru, Indonesia. Employing a quantitative research design, data were collected through surveys administered to teachers across several institutions. The findings reveal that both principal supervision and teacher training exert a significant and positive influence on teachers’ pedagogical competence. Principals’ supervisory practices, when carried out systematically through guidance, feedback, and evaluation, play a pivotal role in enhancing instructional quality. Similarly, targeted and continuous professional training programs equip teachers with the knowledge and skills necessary to adapt to contemporary pedagogical demands, including technology integration and innovative teaching methodologies. The results underscore a synergistic relationship between supervision and training, with statistical analyses indicating that these variables, both independently and collectively, contribute substantially to the development of pedagogical competence. Teachers who receive consistent supervisory support and participate in relevant training demonstrate improved capabilities in lesson planning, classroom management, student assessment, and instructional delivery. These findings highlight the importance of institutional strategies that prioritize sustained supervisory engagement and structured teacher development initiatives as critical pathways for improving teaching effectiveness and educational quality within the madrasah system.